Todo elector republicano puro votará así - Todd, Roberto H. (My University, 1924)
Tarjeta con instrucciones para votar.
Keywords: Elections--Puerto Rico.; Martínez Nadal, Rafael, 1877-1941; Rossy y Calderón, Manuel F., 1861-1932